Unveiling the nature of clusters in the Cygnus region. I. The embedded cluster DB2001–22. Issue 1 (23rd July 2021) - Molina Lera, J A; Gamen, R; Cichowolski, S; Baume, G; Cárdenas, S B
ABSTRACT: The Cygnus region harbours a vast diversity of rich stellar complexes. Hence, it is ideal for studying recently formed stellar clusters, and investigate how the feedback effect and radiation emitted by its massive stars modifies the interstellar medium giving place to induced star forming processes. This is the case of the small and poorly studied cluster DB2001-22. We focus our attention at analysing the cluster and its encompassing region, to distinguish different stellar populations and study their relationship with the surrounding environment. We gleaned literature and data bases for optical and IR photometry, astrometry provided by Gaia eDR3 and spectroscopy, and obtained new infrared Gemini spectra of three young stellar objects candidates (cYSOs). Furthermore, we detected two new massive stars: O7 V and B3 V, in the LAMOST data base, pointing out that DB2001–22 belongs to a much larger complex that involves an entire bubble structure and houses a richer massive population at a distance of 3.0 kpc. In this sense, DB2001–22 and the H ii region G82.6+0.4 are clearly related. Some observed gas and dust structures seem to have been sculpted by these massive stars. Infrared emission is compatible with a hot ionized gas mixed with warm dust surrounded by a structured photo-dissociation region (PDR) scenario. We found nine Class I and 56 Class II cYSOs, whose distribution along the PDR and the tips of pillar structures suggests that their formation may have been induced by the action of the earliest stars in the cluster on to their environment.